1993
DOI: 10.1159/000236581
|View full text |Cite
|
Sign up to set email alerts
|

A Decrease in Reactive Disulfide Bonds of Serum IgG Signals a Characteristic Change in the IgG Subclass Pattern of Rats Bearing Experimental Tumors

Abstract: Previous studies have shown that human IgG1 contains a ‘reactive’ disulfide bridge (SS*), detectable by a 24-hour disulfide exchange reaction, and that the serum level of this IgG subclass is selectively diminished in patients with various malignant diseases. Here we present evidence that in rats IgG2b is the only subclass that carries one SS* per molecule. Furthermore, it is shown that rats inoculated with experimental tumor lines, i.e., the Yoshida hepatoma ascites tumor and the Walker 256 carcinosarcoma gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Experiments are presently under way to examine the hypothesis that malignant tumours may modulate the IgG subclass biosynthesis by the expression of certain cytokines and/or their soluble receptors, which are involved in IgG subclass regulation (Kawano et al, 1994). Whatever the mechanisms are, the regulation of IgG subclasses apparently is extremely sensitive to respective signals derived from malignant cells, which is reflected by the high sensitivity of the phenomenon, particularly for early stages of various tumours in humans (Kronberger et al, 1994;Schauenstein et al, 1996Schauenstein et al, , 1997 including SCC-HN (see present data), and in the rat model (Weblacher et al, 1993). An attractive feature of the IgG subclass shift as tumour marker are the extremely small variation ranges of the single values in normal controls and tumour patients, as compared with several orders of magnitude often observed with conventional tumour markers.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Experiments are presently under way to examine the hypothesis that malignant tumours may modulate the IgG subclass biosynthesis by the expression of certain cytokines and/or their soluble receptors, which are involved in IgG subclass regulation (Kawano et al, 1994). Whatever the mechanisms are, the regulation of IgG subclasses apparently is extremely sensitive to respective signals derived from malignant cells, which is reflected by the high sensitivity of the phenomenon, particularly for early stages of various tumours in humans (Kronberger et al, 1994;Schauenstein et al, 1996Schauenstein et al, , 1997 including SCC-HN (see present data), and in the rat model (Weblacher et al, 1993). An attractive feature of the IgG subclass shift as tumour marker are the extremely small variation ranges of the single values in normal controls and tumour patients, as compared with several orders of magnitude often observed with conventional tumour markers.…”
Section: Discussionmentioning
confidence: 68%
“…In rats it was found that the transplantation of the Yoshida hepatoma or Walker 256 carcinosarcoma cell lines led to an identical IgG subclass shift affecting IgG2b and IgG2a (Weblacher et al, 1993). The data obtained with this model revealed that this tumour-associated phenomenon essentially requires the presence of living, actively dividing tumour cells, that the shift becomes significant long before an exponential tumour growth, and that it is detectable also in the surface expression of the affected IgG subclasses on peripheral blood B lymphocytes .…”
mentioning
confidence: 84%
“…An analogous effect was observed in tumor bearing rats, where the subclass affected was again the one carrying the (SS)* group, i.e. IgG2b [12]. First data in this animal model suggest that proliferating malignant tumors interfere with the regulation of the biosynthesis of IgG subclasses [25].…”
Section: Possible Biological Functions Of(ss)* In Human Lgglmentioning
confidence: 68%
“…[22] + data from ref. [12] § M. Weblacher, unpublished data. These values are on average 72% of those determined in batch with the total IgG (Table 1).…”
Section: Biochemistry and Molecular Biology Internationalmentioning
confidence: 87%
“…Alternatively, the shift might be related to the carcinogenesis process C. F. de la Cruz-Herrera and others itself, as patients with cancer usually show a characteristic and significant alteration in the pattern of serum IgG subclasses, with an increase in IgG2 and a reduction in IgG1 (Schauenstein et al, 1997;Anderhuber et al, 1999). Analogous results have been observed in rodent models (Haddada et al, 1984;Weblacher et al, 1993). In addition, CagA might also be involved in this tumour-associated phenomenon.…”
Section: Discussionmentioning
confidence: 75%